(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
In the article the questions of functional reactions of organism of teenagers are examined on breathing in the conditions of sport activity. It is set that the arbitrary increase of pulmonary ventilation in the conditions of rest comes true by students, going in for sports enough in wide limits, thus both due to making more frequent of breathing and due to the increase of respiratory volume.